Techniques for Sway Control of a Double-Pendulum-Type Overhead Crane - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli; Ahmad Nor Kasruddin, Nasir (United Kingdom Simulation Society, 2010)
This paper presents investigations into the development of input shaping techniques for swaying control of a double-pendulum-type overhead crane (DPTOC) system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. An unshaped bang-bang input force is used to determine the characteristic parameters of the system for design and evaluation of the input shaping control techniques. The positive and modified specified negative amplitude (SNA) input shapers with the derivative effects respectively are designed based on the properties of the system. Simulation results of the response of the DPTOC system to the shaped inputs are presented in time and frequency domains. Performances of the control schemes are examined in terms of sway angle reduction and time response specifications. Finally, a comparative assessment of the proposed control techniques is presented and discussed.